SENSITIVE SPECTROPHOTOMETRIC ASSAY OF MUSCARINIC RECEPTOR ANTAGONIST TOLTERODINE TARTRATE IN BULK DRUG AND PHARMACEUTICAL FORMULATIONS - El-sheikh, Ragaa; Hassan, Wafaa S; Gouda, Ayman A; El-gabry, Marwa M (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Simple, sensitive, and accurate spectrophotometric methods have been developed for the assay of tolterodine tartrate (TOL) in bulk drugand pharmaceutical formulations. Methods: The proposed methods are based on oxidation reaction of TOL with a known excess of cerium(IV) ammonium sulfate as an oxidizing agentin acid medium followed by determination of unreacted oxidant by adding a fixed amount of dye, e.g., amaranth (AM), rhodamine 6G (Rh6G), andindigo carmine (IC) followed by measuring the absorbance at 520, 530, and 610 nm, respectively. The effect of experimental conditions was studiedand optimized. Results: The Beer’s law was obeyed in the concentration ranges of 1.0-10, 1.0-12, and 0.5-9.0 Î¼g/mL using AM, Rh6G, and IC dyes, respectively, witha correlation coefficient â‰¥0.9995. The calculated molar absorptivity values are 1.868Ã—104, 1.008Ã—104, and 1.623Ã—104 L/mol/cm using AM, Rh6G, andIC dyes, respectively. The limits of detection and quantification were reported. Intraday and interday accuracy and precision of the methods have beenevaluated. No interference was observed from the additives. Conclusion: The proposed methods were successfully applied to the assay of TOL in tablets preparations, and the results were statistically comparedwith those of the reported method by applying Student’s t-test and F-test. The reliability of the methods was further ascertained by performingrecovery studies using the standard addition method.